Stolen childhood : slave youth in nineteenth-century America - King, Wilma, 1942- (Blacks in the diaspora., 1997)
Wilma King sheds light on a long-overlooked aspect of slavery in the United States - the wretched lives of the millions of young people enslaved in the nineteenth-century South. A substantial body of scholarship examines the history of U.S. slavery, but it has not focused on these children and their place in enslaved families and the slave community. Wilma King argues that childhood was stolen from these youngsters - they were forced into the workplace at an early age, subjected to arbitrary plantation authority and punishment, and were separated from family. For this exhaustive study, King draws on a wide range of sources, including government records and many unpublished archival materials. This volume tells the story of these children and youth, adding their experience to the history of slavery in the United States.